Methylation of the RELA Gene is Associated with Expression of NF-κB1 in Response to TNF-α in Breast Cancer - Jeong, Young Ju (Molecules, 2019)
The nuclear factor (NF)-κB family of transcriptional factors plays a critical role in inflammation, immunoregulation, cell differentiation, and tumorigenesis. This study aims to investigate the role of methylation of genes encoding for the NF-κB family in breast cancer. We analyze the DNA methylation status of the NFKB1 gene and the RELA gene in breast cancer using pyrosequencing. The expression of NF-κB1 and RELA proteins is assessed and the level of RNA transcripts in frozen tissue is determined using RT-PCR. There is no statistically significant difference in the methylation status of the NFKB1 and the RELA genes between tumors and normal tissues. The methylation status of the NFKB1 gene and the RELA gene is not significantly associated with the levels of NF-κB1 transcripts in tumor tissues. However, the methylation level of the RELA gene is significantly associated with the level of tumor necrosis factor (TNF)-α. In addition, the level of NF-κB1 transcripts was associated with the levels of TNF-α and IL-4. In tumors with positive TNF-α, the increased methylation level of the RELA gene is significantly associated with the positive expression of NF-κB1 transcripts. These results demonstrate that the level of the RELA gene methylation is related to the levels of NF-κB1 transcripts under the influence of TNF-α. Further study is needed to determine how TNF-α is involved in the methylation of the RELA gene and the subsequent expression of NF-κB1.